Electron spectroscopy investigations of semiconductor nanocrystals formed by various technologies. (24th March 2008) - Kovalev, Anatoly I.; Wainstein, D.L.; Tetelbaum, D.I.; Mikhailov, A.N.; Golan, Y.; Lifshitz, Y.; Berman, A.; Basa, P.; Horvath, Zs.J.
The electron spectroscopy techniques (X-ray Photoelectron Spectroscopy (XPS), Auger Electron Spectroscopy (AES), High Resolution Electron Energy Losses Spectroscopy (HREELS), Extended Energy Loss Fine Structure (EELFS) were used for characterisation of semiconductor nanocrystals (Si, PbS, CdS) formed by various technologies: Si ion implantation in Al2O3 matrix and annealing; Si-rich multilayered SiNx Low Pressure Chemical Vapour Deposition (LPCVD); PbS and ZnS nanocrystals on Polydiacetylene (PDA) Langmuir-Blodget polymer films. The chemical, phase and atomic structure non uniformity were determined using depth profiling techniques. The peculiarities of the 'matrix nanocrystal' interface atomic and electronic structure, especially for nanocrystals were determined from analysis of XPS chemical shifts and vibrational spectra. The accommodation strains in the Si-nc:Al2O3 system were determined by EELFS. The comparison of electron spectroscopy methods and other techniques for nanocrystals investigations (PL, HR-TEM, ellipsometry) is made.